2014
DOI: 10.1103/physreva.89.022106
|View full text |Cite
|
Sign up to set email alerts
|

Certainty in Heisenberg's uncertainty principle: Revisiting definitions for estimation errors and disturbance

Abstract: We revisit the definitions of error and disturbance recently used in error-disturbance inequalities derived by Ozawa and others by expressing them in the reduced system space. The interpretation of the definitions as meansquared deviations relies on an implicit assumption that is generally incompatible with the Bell-Kochen-Specker-Spekkens contextuality theorems, and which results in averaging the deviations over a non-positive-semidefinite joint quasiprobability distribution. For unbiased measurements, the er… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 82 publications
(259 reference statements)
0
70
0
Order By: Relevance
“…It has also been shown that the measurement error can be observed experimentally by performing a weak measurement ofÊ a =| a a | on the input state [3,5], and the present discussion was originally motivated by an attempt to understand the physics of these experimental results better [15]. Here, we would like to address the problem that such measurement results cannot be interpreted as a relative frequency of joint outcomes, since the individual weak measurements represent only a statistical preference for the outcome a and not an exclusive selection of a [12]. It is therefore necessary to consider the role of the outcomes a in the experiments more carefully.…”
Section: Error Statistics In Hilbert Spacementioning
confidence: 99%
See 3 more Smart Citations
“…It has also been shown that the measurement error can be observed experimentally by performing a weak measurement ofÊ a =| a a | on the input state [3,5], and the present discussion was originally motivated by an attempt to understand the physics of these experimental results better [15]. Here, we would like to address the problem that such measurement results cannot be interpreted as a relative frequency of joint outcomes, since the individual weak measurements represent only a statistical preference for the outcome a and not an exclusive selection of a [12]. It is therefore necessary to consider the role of the outcomes a in the experiments more carefully.…”
Section: Error Statistics In Hilbert Spacementioning
confidence: 99%
“…In principle, Eq. (12) indicates that any projective measurement {| m } can have a measurement error of ε 2 (A) = 0 if the corresponding set of weak values of m are chosen for the estimatesà m . However, weak values are generally complex, and the imaginary part is usually obtained in a dynamical response of the system that is not directly connected to the quantity represented by [34,35].…”
Section: Error Free Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…The weak value's property of allowing information to be extracted from a quantum system with minimal disturbance is applied as a new method for estimation of quantum states [47][48][49][50] (see [51] for a recent review). This particular property of the weak value is also utilized in experimental tests of a reformulation of Heisenberg's uncertainty principle [52][53][54][55] (an overview of different viewpoints of that topic can be found in [56]). In addition, the weak value and weak measurements have been successfully applied to quantum paradoxes such as the three-box problem [57] and Hardy's paradox [58][59][60].…”
Section: Theoretical Frameworkmentioning
confidence: 99%